2019
DOI: 10.4067/s0034-98872019000500545
|View full text |Cite
|
Sign up to set email alerts
|

¿Qué representa cambiar el umbral diagnóstico de la hipertensión arterial? Guías ACC/AHA 2017 y su aplicación en Perú

Abstract: ¿Qué representa cambiar el umbral diagnóstico de la hipertensión arterial? Guías ACC/AHA 2017 y su aplicación en Perú akram HernándeZ-VásqueZ 1 , CarLos rojas-roque 2,a , mariLina santero 3,4 , juan CarLos ruiZ-maZa 5,b , mixsi Casas-BendeZú 6,c , j. jaime miranda 7,d Changes in the prevalence of hypertension in Peru using the new guideline of the American College of Cardiology Introduction and Objective: There is little evidence in Latin America about the impact of the ACC/AHA 2017 guideline. Taking as refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
1
6
1
6
Order By: Relevance
“…This is in addition to the 1.5 million hypertensive adults currently untreated according to the current (JNC 7) guideline. The relative increase of about 55% in hypertension prevalence as a result of adopting the 2017 ACC/AHA guideline seems to be higher in Chile than those estimated (using similar methods) in the United States (27%), China (45%) and Spain (42%) [11,12], but lower than in Peru (130%) [26]. The definitions in the Peruvian study were based on high BP alone, however, and so is not strictly comparable with our findings.…”
Section: Discussioncontrasting
confidence: 91%
“…This is in addition to the 1.5 million hypertensive adults currently untreated according to the current (JNC 7) guideline. The relative increase of about 55% in hypertension prevalence as a result of adopting the 2017 ACC/AHA guideline seems to be higher in Chile than those estimated (using similar methods) in the United States (27%), China (45%) and Spain (42%) [11,12], but lower than in Peru (130%) [26]. The definitions in the Peruvian study were based on high BP alone, however, and so is not strictly comparable with our findings.…”
Section: Discussioncontrasting
confidence: 91%
“…Likewise, given the differences between the first and second blood pressure measurements in the ENDES, it would be important to have a third measurement. On the other hand, if the American College of Cardiology/American Heart Association 2017 guidelines are applied, it is expected that the prevalence of hypertension and undiagnosed hypertension will increase significantly [ 59 ]. However, the authors consider that the use of a nationally representative database allows the study of a highly prevalent problem such as hypertension, as well as identification of the factors associated with the non-diagnosis of this chronic condition, and consider these findings useful from the Peruvian and global perspective, to continue with the study of the non-diagnosis of hypertension and its related factors.…”
Section: Discussionmentioning
confidence: 99%
“…A national report revealed that hypertension prevalence increased by 0.8 percentage points in the period 2017-2018 [7]. Moreover, the novel cut-off for diagnosis (ACC/AHA 2017, 130/80 mmHg) notably increases the prevalence of hypertension in 18.5 percentage points in comparison with the traditional cut-off (JNC 7, 140/90 mmHg) [8]. This LMIC presents worrying rates of disparities in socioeconomic determinants.…”
Section: Introductionmentioning
confidence: 99%